English Teachers' Professional Development Strategies to Improve Their Competences during Online Teaching at SMPN Batang Anai - Novi Dwi Amelia Putri; Yati Aisya Rani (Journal of English Language Teaching, 2022)
This study aims to find out professional development strategies done by English teachers’ to improve their pedagogic competence and professional competence during online teaching at SMPN Batang Anai. There were 8 English teachers as the research subject of this qualitative. They were interviewed by using the semi-structured interview. The result of the study found that English teachers at SMPN Batang Anai implemented several strategies to improve their pedagogic competence, including team teaching, peer coaching, analyzing critical incidents, and teacher support groups. While to improve their professional competence they have done: self- monitoring, workshop, keeping a teaching journal and case analysis. While, to improve both the pedagogic competence and professional competence of English teachers, it is suggested to them to implemented more and professional development strategies.